Hyperhidrosis: problems and solutions - Stanislava Yu. Petrova; Vera I. Albanova; Konstantin S. Guzev (State Scientific Center of Dermatovenereology and Cosmetology, 2024)
The functional role of sweating is not limited only to thermoregulation and excretion. There are other functions of it - the ability to enhance and maintain hydration and barrier function of the skin. Excessive sweating can lead to an exacerbation or cause many skin diseases, form psychological discomfort in a person due to wet clothes or an accompanying unpleasant odor. Primary hyperhidrosis may be an autosomal dominant genetic disease. Secondary, usually generalized hyperhidrosis is often associated with drug effects on the body or a systemic disease. The following approaches are used in the treatment of hyperhidrosis: 1) blocking the release of sweat to the skin surface (aluminum salts and formaldehyde); 2) physiotherapy (iontophoresis); 3) destruction of sweat glands and cessation of sweat production (excision of a skin flap with subcutaneous fat, curettage, microwave technology, etc.); 4) termination of the signal from the central nervous system to the sweat glands (transthoracic endoscopic sympathectomy, percutaneous radiofrequency sympathectomy, botulinum toxin injections, systemic anticholinergic drugs). External remedies for excessive sweating include the Russian drug Formagel®, containing 3.7% formaldehyde. This drug is a non-invasive, easily doable, effective, safe method of treating hyperhidrosis.